Some Insights into the Impacts of the Islamic Education on the Non-Muslims in Brunei Darussalam - Kumpoh, Asiyah az-Zahra Ahmad (TAWARIKH, 2014)
ABSTRACT: This paper aims to analyse the extent at which the non-Muslims in Brunei Darussalam identify with MIB or âMelayu Islam Berajaâ (Malay Islamic Monarchy), the national philosophy of the country, by investigating the impacts of the Islamic education on the Dusun Muslim converts before their conversion to Islam. The traditionally, animistic Dusuns is one of the constitutionally recognised ethnic groups in the country and is strongly represented in Tutong District. This paper argues that the Dusuns had developed a strong sense of recognition towards Islam, even before their conversion; and this is significantly the result of the decades-long incorporation of the Islamic knowledge into the national education system. The recognition could be seen from the considerable depth of the Islamic knowledge they acquired, where such operative understanding of Islam simultaneously facilitated mutual emulation of Muslim ways of life. As the mutual emulation was also bolstered by the increasing breakdown of social and cultural boundaries between the Dusuns and the Muslims in the country, the informants of this study began to see the appeals and benefits of Islam as a religious system. Such re-appraisal of the religion, eventually led them to forsake their ethnic religion and convert to Islam, a significant step forward in forging a closer identification with the official religion of the country and ultimately with Bruneiâs national philosophy.Â Â  KEY WORDS: Malay Islamic Monarchy, Islamic education, Bruneiâs education policies, the role of education, the Dusuns, and religious conversion.About the Author: Dr. Asiyah az-Zahra Ahmad Kumpoh is a Senior Lecturer at the History Program, Faculty of Arts and Social Sciences UBD (University of Brunei Darussalam), Jalan Tunku Link, Gadong, Negara Brunei Darussalam. For academic purposes, she can be contacted vis her e-mail at: asiyah.kumpoh@ubd.edu.bnHow to cite this article? Kumpoh, Asiyah az-Zahra Ahmad. (2014). âSome Insights into the Impacts of the Islamic Education on the Non-Muslims in Brunei Darussalamâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.161-176. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 18, 2014); Revised (March 19, 2014); and Published (April 28, 2014).